Association of sociodemographic and environmental factors with spatial distribution of tuberculosis cases in Gombak, Selangor, Malaysia - Nur Adibah Mohidem; Malina Osman; Zailina Hashim; Farrah Melissa Muharam; Saliza Mohd Elias; Rafiza Shaharudin (Public Library of Science, 2024)
PLoS ONE 16(6): e0252146